2020
DOI: 10.3389/fmicb.2020.610070
|View full text |Cite
|
Sign up to set email alerts
|

Novel Opportunity to Reverse Antibiotic Resistance: To Explore Traditional Chinese Medicine With Potential Activity Against Antibiotics-Resistance Bacteria

Abstract: Antibiotic resistance is becoming significantly prominent and urgent in clinical practice with the increasing and wide application of antibacterial drugs. However, developing and synthesizing new antimicrobial drugs is costly and time-consuming. Recently, researchers shifted their sights to traditional Chinese medicine (TCM). Here, we summarized the inhibitory mechanism of TCM herbs and their active ingredients on bacteria, discussed the regulatory mechanism of TCM on antibiotic-resistant bacteria, and reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…This finding is in harmony with the former findings, which indicated that K. pneumoniae was the most frequently isolated strain from patients treated in hospitals (2). Moreover, several studies indicated that hospitals and/or clinics are the potential sites for emerging MDR bacterial strains (29,30). Bacteriophages are promising alternative therapeutic agents against multidrug-resistant bacterial pathogens (31).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in harmony with the former findings, which indicated that K. pneumoniae was the most frequently isolated strain from patients treated in hospitals (2). Moreover, several studies indicated that hospitals and/or clinics are the potential sites for emerging MDR bacterial strains (29,30). Bacteriophages are promising alternative therapeutic agents against multidrug-resistant bacterial pathogens (31).…”
Section: Discussionsupporting
confidence: 82%
“…Antibiotic resistance is defined as the ability of bacteria to resist the inhibitory or destructive activity of an antibiotic to which it was initially sensitive [3]. It primarily results from the uncontrolled use of antibacterial drugs both in medicine and in agriculture, which leads to the recurrent exposure of bacteria to sub-lethal doses of antibiotics and results in their adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…This adaptation phenomenon results mainly from the enzymatic degradation of antibiotics by bacteria [4], the modification of the antibiotic target [5], change in membrane permeability [6], and alternative metabolic pathways [6]. Interbacterial transmission of antibiotic resistance through horizontal gene transfer (conjugation, transduction, and transformation) has made the situation critical worldwide [3]. To overcome this problem, intensive research has been done in recent years, and the use of plant extracts and nanoparticle has emerged as promising alternatives [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Another intervention is controlling antimicrobials use, such as selecting novel antimicrobials with limited capacity to ARBs or using fewer antimicrobials. Moreover, traditional Chinese medicines (TCMs) were used in the treatment of infectious diseases to avoid antibiotic resistance ( Cai et al, 2017 ; Su et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%